Can cash break the cycle of educational risks for young children in high HIV-affected communities? A cross-sectional study in South Africa and Malawi - Sherr, L; Tomlinson, M; Macedo, A; Skeen, S; Hensels, I; Cluver, L (Edinburgh University Global Health Society, 2017)
Household cash grants are associated with beneficial outcomes; enhanced if provided in combination with care.This study describes the impact of cash grants and parenting quality on 854 children aged 5-15 (South African and Malawi) on educational outcomes including enrolment, regular attendance, correct class for age and school progress (controlling for cognitive performance). Consecutive attenders at randomly selected Community based organisations were recruited. The effects of cash plus good parenting, HIV status and gender were examined.Overall 73.1% received a grant - significantly less children with HIV (57.3% vs 75.6% (χ2 = 17.21, P < 0.001). Controlling for cognitive ability, grant receipt was associated with higher odds of being in the correct grade (odds ratio (OR) = 2.00; 95% confidence interval (CI) = 1.36, 2.95), higher odds of attending school regularly (OR = 3.62; 95% CI = 1.77, 7.40), and much higher odds of having missed less than a week of school recently (OR = 8.95; 95% CI = 2.27, 35.23). Grant receipt was not associated with how well children performed in school compared to their classmates or with school enrolment. Linear regression revealed that grant receipt was associated with a significant reduction in educational risk (B = -0.32, t(420) = 2.84, P = 0.005) for girls.Cash plus good parenting affected some educational outcomes in a stepwise manner, but did not provide additive protection.